Building efficacy beliefs through team task engagement and past task performance in contemporary teams - Alma Ma Rodríguez-Sánchez; Jari Hakanen; Marisa Salanova (BRQ Business Research Quarterly, 2021)
It is important for organizations to identify the drivers for effective collaboration in contemporary teams, such as self-managed ad hoc teams. Therefore, we aimed to investigate (1) the influence of team task engagement and mastery experiences on collective efficacy beliefs and (2) the temporal relationship between team task engagement and task performance over time. We postulate that to build collective efficacy in contemporary teams over time, it is necessary to enhance positive emotional states (i.e., team task engagement) and mastery experiences (teams' past task performance). The study adopted a three-wave longitudinal design in which 575 individuals nested within 112 self-managed ad hoc teams participated in a decision-making task. Results showed that team task engagement and past task performance positively predicted future collective efficacy. Moreover, team task engagement positively predicted teams' task performance over time. This study contributes to the understanding of the antecedents of team effectiveness, specifically in contemporary teams.
Keywords: C92; J24; O15; 650; collective efficacy; Group decision; social cognitive theory; team performance; team task engagement